2023
DOI: 10.3389/fnut.2023.1279066
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain amino acids metabolism in heart failure

Chenshan Gao,
Lei Hou

Abstract: As a terminal stage of various cardiovascular diseases, heart failure is of great concern due to its high mortality rate and limited treatment options. Researchers are currently focusing their efforts on investigating the metabolism of carbohydrates, fatty acids, and amino acids to enhance the prognosis of cardiovascular diseases. Simultaneously, branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, play significant roles in blood glucose regulation, protein synthesis, and insulin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Accordingly, the hypothesis of energy starvation in HF suggests that mechanisms used to restore energy homeostasis might contribute to the vicious circle leading to cardiac remodeling and HF [ 9 , 10 ]. Indeed, increased glucose uptake and metabolism inhibit the branched-chain amino acid (BCAA) catabolism, promoting the mammalian target of rapamicine (mTOR) activation and cardiomyocyte hypertrophy [ 11 ]. Moreover, the inability to oxidize fatty acids could lead to the accumulation of lipotoxic metabolites [ 12 ].…”
Section: Dysregulation Of Fatty Acid Oxidation In Hfmentioning
confidence: 99%
“…Accordingly, the hypothesis of energy starvation in HF suggests that mechanisms used to restore energy homeostasis might contribute to the vicious circle leading to cardiac remodeling and HF [ 9 , 10 ]. Indeed, increased glucose uptake and metabolism inhibit the branched-chain amino acid (BCAA) catabolism, promoting the mammalian target of rapamicine (mTOR) activation and cardiomyocyte hypertrophy [ 11 ]. Moreover, the inability to oxidize fatty acids could lead to the accumulation of lipotoxic metabolites [ 12 ].…”
Section: Dysregulation Of Fatty Acid Oxidation In Hfmentioning
confidence: 99%
“…However, previous work showed that under normal feeding conditions AAs from CPI and LI are absorbed at slower rates than those from animal proteins, which might explain the lower nutritional utilization of legume storage proteins as compared with LA or CAS [ 4 ]. Lower rates of AAs portal absorption and arterial plasma in rats fed legume proteins may also contribute to a lower risk of processes such as, for example, heart failure, which has been linked to high plasma BCAAs (branch chain amino acids: valine, isoleucine, leucine) levels [ 5 ].…”
Section: Introductionmentioning
confidence: 99%